Effects of aldicarb and fungicides on Pratylenchus penetrans populations, root rot and net blotch severity on barley - Kimpinski, J.; Johnston, H.W. (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ)l, 1995)
Population levels of the root lesion nematode, Pratylenchus penetrans, which produces necrotic lesions in the root cortex, were recorded in barley (Hordeum vulgare) in experimental plots during 1988, 1989, and 1990. Root lesion nematodes were the onlyendoparasitic nematodes recovered from barley roots and were the dominant nematode group found in the soil. Based on 3-yr averages, root rot ratings, caused primarily by Cochliobolussativusand Fusarium spp., increased from 27% at Zadoks Growth Stage (ZGS) 30-32 in July to 73 % at ZGS 70-72 in late August and early September. Net blotch (incited by Pyrenophora teres) was suppressed by a fungicide treatment consisting of a seed application of carbathiin and thiram, and a foliar application of propiconazole. Aldicarb suppressed the populations of root lesion nematodes in the soil, in the total root System, and in crown and seminal roots of barley. Yields were increased by ca 30% where aldicarb and fungicides were applied as a combined treatment. Population densities of root lesion nematodes were much greater in seminal roots than in crown roots at ZGS 30-32 and 55-60. Correlation coefficients between nematodes and yield data were often negative and significant (P≤0.05). There were no consistent trends in the numerical relationships between numbers of root lesion nematodes in roots or soil, and incidences of net blotch or root rot of barley.